THE DIALECTIC OF RELIGION AND LOCAL CULTURE IN THE PRACTICE OF CULTURAL PROPAGATION - Putra Muallimin (NIHAYAH: Journal of Islamic Studies, 2025)
This study examines the dialectical process between Islamic teachings and local culture within the practice of dakwah kultural (cultural propagation) in Indonesia. Employing a qualitative case study approach with ethnographic methods, the research analyzes how this interaction unfolds not as a simple accommodation, but as a dynamic field of negotiation, strategic reinterpretation, and hybrid synthesis. The findings reveal a three-stage, non-linear cycle: strategic adaptation of religious messages into cultural frameworks, contested negotiation often involving tension with puritanical perspectives, and the emergence of contextual syntheses that create locally-grounded, "embedded" Islamic practices. These syntheses, visible in rituals, arts, and social ethics, strengthen communal religious identity and social cohesion. However, the process also faces continuous internal critique and challenges from universalist reform movements, highlighting its contested nature. The study concludes that the sustainability of dakwah kultural depends on maintaining the vitality of this dialectic itself. It recommends the integration of cultural hermeneutics into religious education, the facilitation of structured intergenerational dialogue within communities, and institutional support for creative projects that enable this moderate, contextual model of Islam to adapt to globalizing and digital modernities.